2014
DOI: 10.1007/s10792-014-9944-6
|View full text |Cite
|
Sign up to set email alerts
|

Blue light-filtering intraocular lenses and post-operative mood: a pilot clinical study

Abstract: The purpose of the study was to determine if implantation of blue-filtering intraocular lenses (IOLs) affects post-operative mood, inducing more depression, compared to patients undergoing implantation with conventional IOLs. The study was conducted at the Angers University Hospital, France. This was a prospective with a lowercase pilot study, including consecutive patients planned to undergo cataract surgery in both eyes within 1 week. The same type of IOL was used in both eyes of each patient. The choice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…However, the PIPR did not differ between patients with blue-blocking IOLs versus neutral IOLs. Other studies have found that short-term improvements in sleep quality and depression scores following lens replacement are equivalent for IOLs that filter blue light versus those that only block UV light626364. These findings suggest that reduced transmission of blue light with IOLs might have limited clinical impact on non-visual light responses, similar to our findings for the pupillary light reflex in nonpathalogical aging.…”
Section: Discussionsupporting
confidence: 86%
“…However, the PIPR did not differ between patients with blue-blocking IOLs versus neutral IOLs. Other studies have found that short-term improvements in sleep quality and depression scores following lens replacement are equivalent for IOLs that filter blue light versus those that only block UV light626364. These findings suggest that reduced transmission of blue light with IOLs might have limited clinical impact on non-visual light responses, similar to our findings for the pupillary light reflex in nonpathalogical aging.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, 16 articles that met the inclusion criteria were included in the meta‐analysis (Table S1). 22‐37 …”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 1996 and 2018 and included a total number of 1308 patients who underwent cataract surgery. Five of them were conducted in the United States, 23,24,30,31,34 two in China, 29,33 two in Japan, 25,35 two in Vietnam, 22,36 one in the United Kingdom, 26 one in Iran, 27 one in France, 28 one in Greece 32 and one in Australia 37 . The duration of the follow up ranged from 1 to 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only three non-randomized studies have compared the effects of clear and yellow IOLs on circadian rhythms with a focus on sleep. One study involved 34 patients (Leruez et al, 2015), another study included 49 patients (Landers, Tamblyn, & Perriam, 2009), and another larger study included 961 patients (Alexander et al, 2014). None of these studies reported differences regarding quality of life or quality of sleep between patients in the clear or yellow IOLs groups.…”
Section: Introductionmentioning
confidence: 99%